2020
DOI: 10.7759/cureus.9622
|View full text |Cite
|
Sign up to set email alerts
|

Xia-Gibbs Syndrome: A Rare Case Report of a Male Child and Insight into Physiotherapy Management

Abstract: Xia-Gibbs syndrome (XGS) is a recently discovered genetic disorder. It is characterized by global developmental delay, intellectual impairment, hypotonia, and sleep abnormalities. While the current literature emphasizes on the genotype and phenotype of this rare condition, it does not provide any description of the physiotherapy management of patients with XGS. We report a case of a 27-month-old Indian male diagnosed with XGS, who presented with difficulty in sitting without support. He had dysmorphic facies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Damage to DNA, which contains the blueprint of protein synthesis, influences and ultimately alters brain development, consequently painting the clinical picture of XGS [ 5 , 32 ]. The striking features of XGS are cognitive impairment, delayed development, expressive language delay, brain structure anomalies, low tone, dysmorphic facies, vision issues, and poor quality sleep [ 1 - 4 , 9 , 12 , 13 , 33 - 35 ]. Sleep apnea has been described in many patients with polysomnographic confirmation.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Damage to DNA, which contains the blueprint of protein synthesis, influences and ultimately alters brain development, consequently painting the clinical picture of XGS [ 5 , 32 ]. The striking features of XGS are cognitive impairment, delayed development, expressive language delay, brain structure anomalies, low tone, dysmorphic facies, vision issues, and poor quality sleep [ 1 - 4 , 9 , 12 , 13 , 33 - 35 ]. Sleep apnea has been described in many patients with polysomnographic confirmation.…”
Section: Reviewmentioning
confidence: 99%
“…Although aggression is not a common finding, self-injurious behaviour has been reported in a few children diagnosed with XGS [ 2 , 4 , 9 , 12 ]. In August 2020, Goyal et al also reported unilateral ptosis and scoliosis in an Indian child diagnosed with XGS [ 35 ]. Dysmorphic features of the face include depressed nasal bridge, hypertelorism, downslanting or upslanting palpebral fissures, horizontal eyebrows, dysplastic dentition, thin upper lip vermilion, and micrognathia [ 1 , 4 , 9 , 12 , 13 , 30 , 35 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations